Literature as ethics: Stanley Cavell, Robert Musil, and the scope of moral perfectionism - Blok, Mette (Res Cogitans, 2018)
“But can philosophy become literature and still know itself?” With this pointed question the American philosopher Stanley Cavell famously ended his monumental work The Claim of Reason (1979), thereby expressing his vision for the relation between philosophy and literature.